Single-photon imaging - Seitz, Peter; Theuwissen, Albert J.P (New York SpringerLink, 2011)
The acquisition and interpretation of images is a central capability in almost all scientific and technological domains. In particular, the acquisition of electromagnetic radiation, in the form of visible light, UV, infrared, X-ray, etc. is of enormous practical importance. The ultimate sensitivity in electronic imaging is the detection of individual photons. With this book, the first comprehensive review of all aspects of single-photon electronic imaging has been created. Topics include theoretical basics, semiconductor fabrication, single-photon detection principles, imager design and applications of different spectral domains. Today, the solid-state fabrication capabilities for several types of image sensors has advanced to a point, where uncoooled single-photon electronic imaging will soon become a consumer product. This book is giving a specialist´s view from different domains to the forthcoming ?single-photon imaging? revolution. The various aspects of single-photon imaging are treated by internationally renowned, leading scientists and technologists who have all pioneered their respective fields.
Fundamentals of noise in optoelectronics -- Semiconductor technology for single-photon image sensing -- Hybrid Avalanche Photodiode Array (APD) Imaging -- Electron Bombarded Semiconductor Image Sensors -- Silicon Photomultipliers, SiPM -- Electron-Multiplying CDs, EMCCD -- Monolithic Single-Photon Avalanche Photodetectors, SPAD -- Single-photon CMOS imaging through bandwidth optimization -- Architectures for low-noise CMOS electronic imaging -- Low-noise electronic imaging with double-gate FETs and charge-modulation devices -- Energy-sensitive single-photon X-ray and particle imaging -- Single-photon imaging for astronomy and aerospace applications -- Single-photon imaging for the life sciences -- Single-photon imaging for time-of-flight range 3D imaging.
Keywords: Optoelectronics; Imaging systems; Electronic books